A publicidade abusiva em face da hipossuficiência da criança - Fonteles, Brice Sampaio Teles (2009)
The present dissertation approaches publicity aimed at children, specifically the one which is shown on television media. It is here emphasized problems generated by childhood consumerism and how this consumeristic behavior is related to publicity aimed at children. Brazilian Consumer Protection Code considers the publicity aimed at children abusive because it takes advantage of the lack of experience and ability to judge attributed to children, who are still developing individuals, and for this reason have their rights broadly secured by the Brazilian Federal Constitution of 1988 and the Brazilian Child and Adolescent Statute. The encounter of these three set of laws establishes a complete protection system that makes publicity aimed at children intrinsically illegal. In conclusion, this restriction could coexist with the state of democratic rights, considering citizenship development based on infancy protection, which could be secured by laws or by the civil society as a whole.